STRIVING FOR SUPERIORITY IN MATTHEW PENRY-DAVEY'S LORD OF WAR MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - MARTURIANINGSUM, EMA (2010)
This research paper is aimed at analyzing the. The researcher analyzes striving for superiority feeling in Matthew Penry-Davey's Lord of War movie. The researcher analyzes the main character who is Yuri Orlov in striving his superiority in becoming the best arm dealer in the world. He involved his brother, Vitaly Orlov in his search of superiority in arm dealing, but he lost his brother. The problem statement of this research paper is that how the struggle for superiority is reflected in the world of arm-trafficking business in Lord of War movie. Therefore, the objective of this research paper is 1) to analyze the movie based on its structural elements, and 2) to analyze the main character's (Yuri Orlov) personality based on the individual psychological perspective. The movie has fulfilled the structural element of a movie. Meanwhile the individual psychological perspective of Yuri Orlov in striving for superiority is that he tries to attempt anything to strive for his superiority in arm dealing. Even when he should sacrifice his brother, he would still sell arm in illegal way. He even tried to hide what he is doing from his family.